Evidence, memory, identity, and community: four shifting archival paradigms - Cook, Terry (Archival Science, 2013)
This essay argues that archival paradigms over the past 150 years have gone through four phases: from juridical legacy to cultural memory to societal engagement to community archiving. The archivist has been transformed, accordingly, from passive curator to active appraiser to societal mediator to community facilitator. The focus of archival thinking has moved from evidence to memory to identity and community, as the broader intellectual currents have changed from pre-modern to modern to postmodern to contemporary. Community archiving and digital realities offer possibilities for healing these disruptive and sometimes conflicting discourses within our profession.
Other Publications
Keywords: A&DwP website; Archival theory; Community archiving; Evidence; Memory; Paradigm shifts; Professional identity

Invoking “collective memory”: mapping the emergence of a concept in archival science - Jacobsen, Trond; Punzalan, Ricardo L.; Hedstrom, Margaret L. (Archival Science, 2013)
The concept of “collective” or “social” memory has assumed increasing prominence in the discourse of archivists over the past few decades. Archives are frequently characterized as crucial institutions of social memory, and many professional activities are considered forms of memory preservation. We present a systematic examination of the relationships between archives and collective memory as articulated in the English-language archival literature. We first identify the major themes regarding collective memory and categorize archival writings into four major threads. We then analyze citations extracted from 165 articles about collective memory published between 1980 and 2010 in four leading English-language archival studies journals. We identify the most influential scholars and publications and trace the evolution of the collective memory concept in that literature. By comparing the archival literature on collective memory to that indexed in Thomson’s Web of Science and in Google Scholar, we identify specific disciplines, authors, and works that archivists working on collective memory may find useful. We find that in general the archival literature on collective memory is fairly insular and self-referential and call on archivists to actively engage other disciplines when carrying out collective memory research.
Other Publications
Keywords: A&DwP website; Archives and memory; Citation analysis; Collective memory; Public memory; Social memory; Transdisciplinarity

Norwegian war children's work for justice - the role of the archives - Olsen, Kåre (Comma, 2013)
People from different weak groups struggling for justice may be dependent on archive material to document and substantiate their claims. In this paper I discuss the question of to what extent we as archivists are aware of our role as rulers of the archives. As an example, I use the Norwegian war children and the importance of information from the archives of the Norwegian National Archives for them both individually and as a group in society. I also discuss how we as Civil Servants and archivists can perform in our work in a professional way when we are aware of the potential significance our role may have for users from weak groups and their work for justice.
Other Publications

Iron Curtain: The Crushing of Eastern Europe, 1944-1956 - Applebaum, Anne (Knopf Doubleday Publishing Group, 2013)
National Book Award Finalist TIME Magazine's #1 Nonfiction Book of 2012A New York Times Notable BookA Washington Post Top Ten Book of 2012Best Nonfiction of 2012: The Wall Street Journal, The Plain Dealer In the much-anticipated follow-up to her Pulitzer Prize-winning Gulag, acclaimed journalist Anne Applebaum delivers a groundbreaking history of how Communism took over Eastern Europe after World War II and transformed in frightening fashion the individuals who came under its sway. Iron Curtain describes how, spurred by Stalin and his secret police, the Communist regimes of Eastern Europe were created and what daily life was like once they were complete. Drawing on newly opened East European archives, interviews, and personal accounts translated for the first time, Applebaum portrays in chilling detail the dilemmas faced by millions of individuals trying to adjust to a way of life that challenged their every belief and took away everything they had accumulated. As a result the Soviet Bloc became a lost civilization, one whose cruelty, paranoia, bizarre morality, and strange aesthetics Applebaum captures in these electrifying pages.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Archives for a Peaceful Future: A Guidance Note for Working with the Archives of Truth Commissions in Dealing with the Past - Rubli, Sandra (Swisspeace, 2013)
Google-Books-ID: CisEswEACAAJ
Keywords: References - Boel et al. (2021); Archives and Human Rights

Senegal: Obama Backs Hissène Habré Court - Human Rights Watch (Human Rights Watch, 2013)
President Barack Obama’s endorsement of Senegal’sefforts to bring to book the former Chadiandictator Hissène Habré is a recognition of the case’s importance for African justice.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Overcoming the apartheid legacy: the special case of the Freedom Charter - Dominy, Graham (Archival Science, 2013)
This paper outlines the construction of the ‘‘ofﬁcial’’ archives of the South African apartheid state and the distorted view they contain concerning social and political realities. Therefore, the colonial and apartheid legacies are examined in a broader context as an oppressive social and political system, as well as in the more speciﬁc context of how their legacy is reﬂected in the ofﬁcial archives. The development and popular endorsement of the Freedom Charter of 1955 was a seminal moment of challenge to the increasing oppression of the apartheid state. In later decades, the Freedom Charter became an iconic reference point in the antiapartheid struggle and the inspiration for the construction of a constitutional democracy in the 1990s. The process of its creation stands in stark contrast to the processes of creation of ofﬁcial records and archives. The paper also examines the survival of the Freedom Charter and the struggle to save it from auction in London and secure its safe passage to the National Archives of South Africa. Finally, questions of meaning and ideological signiﬁcance are asked in relation to the role of a National Archives in the current dominant historical narrative.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Caribbean Nations to Seek Reparations, Putting Price on Damage of Slavery - Castle, Stephen (The New York Times, 2013)
Fourteen countries plan to compile an inventory of the harm caused by the slave trade and then demand an apology and reparations from the former colonial powers Britain, France and the Netherlands.
Keywords: Antigua and Barbuda; Caribbean Area; Castle; Stephen; France; Great Britain; Haiti; Netherlands; References - Boel et al. (2021); Archives and Human Rights; Reparations; Slavery

UK to compensate Kenya's Mau Mau torture victims - Press Association (The Guardian, 2013)
William Hague says payments totalling £19.9m represent 'full and final settlement' of action brought by five victims of torture
Keywords: Africa; Foreign policy; Kenya; Law; Mau Mau; Politics; References - Boel et al. (2021); Archives and Human Rights; Torture; UK news; William Hague; World news

International Principles on the Application of Human Rights to Communications Surveillance - Necessary & Proportionate (Necessary & Proportionate, 2013)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Securing Police Archives. A Guide for Practitioners - Peterson, Trudy Huskamp (Swisspeace, 2013)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Human Rights Indicators: A Guide to Measurement and Implementation - United Nations Human Rights (United Nations, 2013)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Judgement Volume 2 of 6 - United Nations (United Nations, 2013)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

First, Do No Harm: The US Sexually Transmitted Disease Experiments in Guatemala - Rodriguez, Michael A.; García, Robert (American Journal of Public Health, 2013)
Beginning in 1946, the United States government immorally and unethically—and, arguably, illegally—engaged in research experiments in which more than 5000 uninformed and unconsenting Guatemalan people were intentionally infected with bacteria that cause sexually transmitted diseases. Many have been left untreated to the present day., Although US President Barack Obama apologized in 2010, and although the US Presidential Commission for the Study of Bioethical Issues found the Guatemalan experiments morally wrong, little if anything has been done to compensate the victims and their families., We explore the backdrop for this unethical medical research and violation of human rights and call for steps the United States should take to provide relief and compensation to Guatemala and its people.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

René Cassin and Human Rights: From the Great War to the Universal Declaration - Winter, Jay; Prost, Antoine (Cambridge University Press, 2013)
Through the life of one extraordinary man, this biography reveals what the term human rights meant to the men and women who endured two world wars, and how this major political and intellectual movement ultimately inspired and enshrined the Universal Declaration of Human Rights. René Cassin was a man of his generation, committed to moving from war to peace through international law, and whose work won him the Nobel Peace Prize in 1968. His life crossed all the major events of the first seventy years of the twentieth century, and illustrates the hopes, aspirations, failures and achievements of an entire generation. It shows how today's human rights regimes emerged from the First World War as a pacifist response to that catastrophe and how, after 1945, human rights became a way to go beyond the dangers of absolute state sovereignty, helping to create today's European project.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

News from the ICA Human Rights Working Group - 2013-12 (December) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-11 (November) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-10 (October) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-09 (September) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-08 (August) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-07 (July) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-06 (June) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-05 (May) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-04 (April) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-03 (March) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-02 (February) - Peterson, Trudy Huskamp (ICA, 2013)

News from the ICA Human Rights Working Group - 2013-01 (January) - Peterson, Trudy Huskamp (ICA, 2013)